Divergent host humoral innate immune response to the smooth-to-rough adaptation of Mycobacterium abscessus in chronic infection - Wheeler, Emily A.; Lenhart-Pendergrass, Patricia M.; Rysavy, Noel M.; Poch, Katie R.; Caceres, Silvia M.; Calhoun, Kara M.; Serban, Karina A.; Nick, Jerry A.; Malcolm, Kenneth C. (Frontiers in Cellular and Infection Microbiology, 2025)
Mycobacterium abscessus is a nontuberculous mycobacterium emerging as a significant pathogen in individuals with chronic lung diseases, including cystic fibrosis and chronic obstructive pulmonary disease. Current therapeutics have poor efficacy. Strategies of bacterial control based on host defenses are appealing; however, antimycobacterial immunity remains poorly understood and is further complicated by the appearance of smooth and rough morphotypes, which elicit distinct host responses. We investigated the role of serum components in neutrophil-mediated clearance of M. abscessus morphotypes. M. abscessus opsonization with complement enhanced bacterial killing compared to complement-deficient opsonization. Killing of rough isolates was less reliant on complement. Complement C3 and mannose-binding lectin 2 (MBL2) were deposited on M. abscessus morphotypes in distinct patterns, with a greater association of MBL2 on rough M. abscessus. Killing was dependent on C3; however, depletion and competition experiments indicate that canonical complement activation pathways are not involved. Complement-mediated killing relied on natural IgG and IgM for smooth morphotypes and on IgG for rough morphotypes. Both morphotypes were recognized by complement receptor 3 in a carbohydrate- and calcium-dependent manner. These findings indicate a role for noncanonical C3 activation pathways for M. abscessus clearance by neutrophils and link smooth-to-rough adaptation to complement activation.